Amyotrophic Lateral Sclerosis. Surgical experience in 13 patients - Hernando Rafael (2013)
Introduction: In August 2009 we performed surgery for the first time in a patient with amyotrophic lateral sclerosis (ALE). However, every published report about ALE mentions there is no cure for this condition. Objective: To prove that the progression of ALE may be stopped and the condition may be improved using an epiplon transplant. Material and Method: This report presents our experience with 13 ALE patients, affected by the bulbar and spinal forms of the disease. During the surgical procedures, we made the following findings: 1) anatomical variants in the V4 segment of vertebral arteries, 2) moderate or severe atherosclerosis in both V4 segments, 3) some circumflex blood vessels originating from the low-flow anterior and ventral spinal arteries, 4) hypothrophy of small nerve roots in the pathway of IX, X, and XI cranial nerves, 5) in some cases, hypothrophy of the anterior surface of the pyramids, and 6) hypothrophy of the anterior roots in C5 - C6. Every patient underwent an epiplon transplant upon the anterior, lateral, and posterior aspects of the medulla oblongata, and 5 patients underwent an additional transplant performed upon the C5-C6 territory. Results: Neurological improvement was seen from the first postoperative day, and it reached its maximum level during the first few days or weeks after surgery. Nowadays, 2 patients after eight and twelve months after surgery have had a 90% symptomatic improvement of the bulbar form of ALE.   Conclusion: These results indicate that the bulbar form of ALE is caused by progressive ischemia in the parenchymal territory irrigated by the anterior and ventral spinal arteries, and that the spinal form is caused by ischemia in the anterior spinal artery, affecting the area between C5 and T1. This may explain why this revascularization procedure using epiplon tissue led to neurological improvement.